Cinderella in Babylon: the representation of housekeeping and housekeepers in the UK television series Hotel Babylon - Harris, C; Tregidga, H; Williamson, D (Intellect Ltd, 2011)
This article examines representations of housekeeping and housekeepers in the popular television series Hotel Babylon. We take a reflective approach in consid-ering how identities and roles in the Hotel Babylon series are constructed, regarding the housekeeping department and its workers. We identify that the representation of housekeeping work and employees is one of mainly sexualized victims, migrant workers and denigrated employees. Some possible effects of the identity and role constructed in this series are discussed; in particular an under-mining and undervaluing of a career in housekeeping. This study suggests more fundamental concerns about sustaining service quality and employment relation-ships in the hotel sector.
Keywords: Hotel Babylon; Housekeeping; Representation; Migrants; Sexualization